Agricultural marketing boards : their establishment and operation - Abbott, John Cave.; Creupelandt, H. C. (Rome : Food and Agriculture Organization of the United Nations, 1966)
The purpose of this guide is to provide practical advice on the conditions and goals for which a marketing board or similar organization is a useful mechanism, and on how it can be operated successfully. The text is designed primarily for use in developing countries where subsidization of marketing operations from the nonagricultural sector is rarely feasible.
Includes index.
Includes bibliographical references: p. 229-231
ne 22/01/2019
Loans
Keywords: Agriculture and state; Farm produce--Marketing.; Agriculture--Economic aspects; Marketing boards